Peranan Pendidikan Agama Islam Terhadap Prilaku Kenakalan Remaja - Siska Afriany; Diah Sartika; Hasrian Rudi Setiawan (Yayasan Rahmat Islamiyah, 2023)
Islamic religious education has a very important meaning for the development of children, especially teenagers, namely as a foundation that aims to increase students' faith and piety and practice of Islamic teachings. Islamic religious education should be given special attention in forming the character of teenagers in dealing with juvenile delinquency. Daily reality shows that there are still many students in their teenage years who commit mischief, some of whom do not comply with the rules that apply at home, school or in the community. The forms of delinquency that exist are in the form of group delinquency, such as fights between students, riots racing, bullying groups and so on. Factors that influence juvenile delinquency are personal, family, school and environmental factors. Islamic religious education is provided optimally to minimize juvenile delinquency. Preventive efforts to tackle juvenile delinquency include involving teenagers in religious activities and other positive activities so that they can form positive characters.